On translating titles of literary works - Adwedyk, Sława (Folia Scandinavica Posnaniensia, 2007)
In the paper translations of titles of literaiy works are discussed. The author analyses translations of titles of some Norwegian novels into Polish. The first part of the paper describes the distinction between translation of formal and dynamic equivalence. The analysis has been focused on one aspect, namely, whether the Polish title has an equivalent effect on the receptors.